Advancement in liver laparoscopic resection - development of a new surgical device - Vavra, P; Karnik, L; Skrobankova, M; Jurcikova, J; Ihnat, P; Zonca, P; Peteja, M; El-Gendi, A; Czudek, S (Brazilian journal of medical and biological research, 2018)
Liver resection is the standard treatment for any liver lesion. Laparoscopic liver resection is associated with lower intra-operative blood loss and fewer complications than open resection. Access to the posterior part of the right liver lobe is very uncomfortable and difficult for surgeons due the anatomic position, especially when employing laparoscopic surgery. Based on these experiences, a new laparoscopic device was developed that is capable of bending its long axis and allowing the application of radiofrequency energy in areas that were not technically accessible. The device is equipped with four telescopic needle electrodes that cause tissue coagulation after the delivery of radiofrequency energy. Ex vivo testing was performed in 2012 and 2014 at the University Hospital, Ostrava, on a porcine liver tissue. The main goal of this testing was to verify if the newly proposed electrode layout was suitable for sufficient tissue coagulation and creating a safety zone around lesions. During the ex vivo testing, the material of needle electrodes was improved to achieve the lowest possibility of adhesion. The power supply was adjusted from 20 to 120 W and the ablation time, which varied from 10 to 110 s, was monitored. Subsequently, optimal power delivery and time for coagulation was determined. This experimental study demonstrated the feasibility and safety of the newly developed device. Based on the ex vivo testing, LARA-K1 can create a safety zone of coagulation. For further assessment of the new device, an in vivo study should be performed.
Keywords: hemostáza chirurgická; Laparoscopy; Hemostasis, Surgical; Liver; lidé; katetrizační ablace; laparoskopie; játra; hepatektomie; Hepatectomy; Humans; Catheter Ablation; Equipment Design; design vybavení